(untitled) (Journal of University of Babylon for Engineering Sciences, 2024)
The outdoor uses of visible light communications (VLC) technology have received less attention than their interior counterparts. This is because the level of interference and noise in outdoor VLC is significantly higher; many other communication technologies are available for use that, due to their unique characteristics, adapt better to the outdoor environment when compared to VLC technology; and the dual use of light emitting diodes (LEDs) is not always practicable in the outdoor VLC environment. There are numerous obstacles in the way of implementing these communication networks. The majority of them are associated with environmental elements like sunlight, fog, rain, dust, snow, and atmospheric disturbances. The impact of fog and rain on visible light communication (VLC) has been the subject of several studies. These environmental conditions can significantly affect the performance of VLC systems. Fog and rain can cause attenuation and scattering of the light signal, leading to an increase in the bit error rate (BER) and a reduction in the communication range. The semi-conductor laser chaos generation is now being utilized to improve data security and protect data from theft during its transmission from transmitter to receivers